2017
DOI: 10.1002/mp.12668
|View full text |Cite
|
Sign up to set email alerts
|

Ion recombination and polarity correction factors for a plane–parallel ionization chamber in a proton scanning beam

Abstract: Purpose: To evaluate the effect on charge collection in the ionization chamber (IC) in proton pencil beam scanning (PBS), where the local dose rate may exceed the dose rates encountered in conventional MV therapy by up to three orders of magnitude. Methods:We measured values of the ion recombination (k s ) and polarity (k pol ) correction factors in water, for a plane-parallel Markus TM23343 IC, using the cyclotron-based Proteus-235 therapy system with an active proton PBS of energies 30-230 MeV. Values of k s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Increased chamber bias (within the chamber-bias specification range) may also reduce recombination in some cases. Finally, polarity corrections must also be considered, but they are typically negligible in proton beams for plane-parallel chambers 154,155 .…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Increased chamber bias (within the chamber-bias specification range) may also reduce recombination in some cases. Finally, polarity corrections must also be considered, but they are typically negligible in proton beams for plane-parallel chambers 154,155 .…”
Section: Accepted Articlementioning
confidence: 99%
“…Finally, polarity corrections must also be considered, but they are typically negligible in proton beams for plane-parallel chambers. 154,155 In summary, the uncertainties associated with absorbed dose calibration of proton beams can be classified as intrinsic and practice dependent. The inherent uncertainties stem from the physical characteristics of the ionization chamber and its 60 Co calibration.…”
Section: D3 Calibration Ionization Chamber Choice and Absolute Domentioning
confidence: 99%
“…Rossomme et al . and Liszka et al . showed that, even if the dose distribution at a particular time is not uniform within the volume of the ionization chamber, the same models can be applied to scanned beams (and more generically to any nonuniform beam) if an effective ionization density or current is taken into account.…”
Section: Detectors For Measurements Of Absorbed Dose In Reference Conmentioning
confidence: 99%
“…These models, which have been confirmed in numerous experimental studies, are the basis of the two-voltage method proposed by Boag and Currant. 76 Rossomme et al 72 and Liszka et al 77 showed that, even if the dose distribution at a particular time is not uniform within the volume of the ionization chamber, the same models can be applied to scanned beams (and more generically to any nonuniform beam) if an effective ionization density or current is taken into account. A similar aspect is the time-dependent structure of absorbed dose delivery in the SOBP of a clinical particle beam which can be accounted for by the use of an effective ionization current.…”
Section: B1 Protocols (Aapm 16 Icru 59 78 Eched Iaea)mentioning
confidence: 99%
“…Pencil beam scanning typically employs large dose rates along the beam axis; therefore, studies about dose-rate dependent detector effects have been performed, even before FLASH became an important topic. Liszka et al [31] found small variation in recombination visible already at clinical dose rates; in particular, they found that recombination corrections estimated at an isochronous-cyclotron facility increase as a function of dose-rate. Such recombination correction variations are usually neglected in clinical practice, either because of their size (less than 0.5% in a clinical volume) or because the variations in dose rates are compensated by the accelerator system by extracting lower currents at higher energies, therefore keeping the dose rate constant at the patient.…”
Section: Control and Monitoringmentioning
confidence: 99%